Ex-stasis and Acting Methods: Eisenstein and Ignacio de Loyola’s ‘Spiritual Exercises’ - Camuti, Fabiola (SigMa - Rivista di Letterature comparate, Teatro e Arti dello spettacolo, 2023)
This paper addresses the in-depth study and interest of Sergei Mikhailovich Eisenstein in Ignacio de Loyola’s Spiritual Exercises, related to the Jesuit practice. It demonstrates that Eisenstein not only calls upon Loyola’s teaching in his theorization of pathos and ecstasy, but that he especially does so also to draw upon specific characteristics of well-known and established Western theatre acting methods. This second reference is mostly unknown to the Anglo-Saxon speaking academic field because of the lack of English translations of the specific essay in which Eisenstein constructs his parallelism between the Jesuit exercises and the work of the Stanislavskian actor. In fact, in the official English edition of Eisenstein’s writings this specific passage, which is present in the Italian publication, was left out because of editorial choices. The paper aims at underlining the importance of Eisenstein’s interests in the Jesuit spiritual traditions in outlining the idea of the practice of acting as an attraction in his theorisation of montage.